Pengaruh Promosi Simpanan BMT NU Bluto terhadap Minat Menabung Pengrajin Batik di Desa Pakandangan Barat - Fajri, Faizar Zaky; Toha, Mashuri (Assyarikah: Journal of Islamic Economic Business, 2025)
As the banking sector continues to evolve, promotional strategies play a pivotal role in enabling financial institutions to attract, engage, and retain their target markets. A well-executed promotion can significantly influence the inclination of potential clients—in this case, batik artisans in Pakandangan Barat Village—to save or become members of the BMT NU Bluto branch. This study aims to examine the extent to which BMT NU Bluto’s promotional activities affect the saving interest of these artisans. Utilizing a quantitative correlational approach, data were collected from 40 respondents and analyzed through simple linear regression using SPSS software. The findings reveal that promotional efforts exert a statistically significant influence on saving interest (t-count = 9.424 > t-table = 2.026; p-value = 0.000 < 0.05), with an R² value of 0.700, indicating that 70% of the variance in saving interest is attributable to promotional activities. These results underscore the crucial role of promotion in enhancing the saving interest of local batik artisans.